Genome-wide comparative analysis in Solanaceous species reveals evolution of microRNAs targeting defense genes in Capsicum spp. (27th July 2018) - Seo, Eunyoung; Kim, Taewook; Park, June Hyun; Yeom, Seon-In; Kim, Seungill; Seo, Min-Ki; Shin, Chanseok; Choi, Doil
Abstract: MicroRNAs (miRNAs) play roles in various biological processes in plants including growth, development, and disease resistance. Previous studies revealed that some plant miRNAs produce secondary small interfering RNAs (siRNAs) such as phased, secondary siRNAs (phasiRNAs), and they regulate a cascade of gene expression. We performed a genome-wide comparative analysis of miRNAs in Solanaceous species (pepper, tomato, and potato), from an evolutionary perspective. Microsynteny of miRNAs was analysed based on the genomic loci and their flanking genes and most of the well-conserved miRNA genes maintained microsynteny in Solanaceae. We identified target genes of the miRNAs via degradome analysis and found that several miRNAs target many genes encoding nucleotide-binding leucine-rich repeat (NLR) or receptor-like proteins (RLPs), which are known to be major players in defense responses. In addition, disease-resistance-associated miRNAs trigger phasiRNA production in pepper, indicating amplification of the regulation of disease-resistance gene families. Among these, miR-n033a-3p, whose target NLRs have been duplicated in pepper, targets more NLRs belonging to specific subgroup in pepper than those in potato. miRNAs targeting resistance genes might have evolved to regulate numerous targets in Solanaceae, following expansion of target resistance genes. This study provides an insight into evolutionary relationship between miRNAs and their target defense genes in plants.